Video in Vertical Format in Spanish Digital Media - Navarro Güere, Héctor; Massana Molera, Eulàlia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The growing dominance of mobile devices and the consumption of news make it possible to foresee changes in the news offer and formats offered by the digital media. The video format is characterised by brevity and constant updating and has a greater interaction with the audience. This paper studies the expressions of the image in vertical format of nine Spanish media with profiles on TikTok, Instagram Reels and YouTube Shorts. The following have been identified: formal characteristics; differences between digital media and social platforms; hybridisation of traditional audiovisual practices with more recent ones.